When should I attempt my centrally administered summative assessments in the RANZCP competency-based training program?. (December 2016) - Kealy-Bateman, Warren; Kotze, Beth; Lampe, Lisa
Objective: To provide information relevant to decision-making around the timing of attempting the centrally administered summative assessments in the Royal Australian and New Zealand College of Psychiatrists (RANZCP) 2012 Fellowship Program. Methods: We consider the new Competency-Based Fellowship Program of the RANZCP and its underlying philosophy, the trainee trajectory within the program and the role of the supervisor. The relationship between workplace-based and external assessments is discussed. The timing of attempting centrally administered summative assessments is considered within the pedagogical framework of medical competencies development. Results: Although successful completion of all the centrally administered summative assessments requires demonstration of a junior consultant standard of competency, the timing at which this standard will most commonly be achieved is likely to vary from assessment to assessment. There are disadvantages attendant upon prematurely attempting assessments, and trainees are advised to carefully consider the requirements of each assessment and match this against their current level of knowledge and skills. Conclusions: Trainees and supervisors need to be clear about the competencies required for each of the external assessments and match this against the trainee's current competencies to assist in decision-making about the timing of assessments and planning for future learning.